Training on ant sugar production to increase people's income in Ba'ka Village, Enrekang - Syarif, Irman; Agusriandi, Agusriandi; Elihami, Elihami; Samad, Ita Sarmita; Wahyuni R, Sry (Universitas Muhammadiyah Magelang, 2021)
Most of the people of Ba'ka Village are conventional palm sugar farmers whose whose selling prices are cheap. The purpose of this service is to provide innovation in palm sugar into ant sugar. Through training in making ant sugar, it is hoped that it can increase people's income. The stages of community service include needs analysis, problem formulation, work program formulation, and work program implementation, and evaluation. This service activity produces ant sugar products that are packaged in a modern way. Ant sugar products can attract consumers because they are more durable, hygienic, and practical.